STRATEGI PERPUSTAKAAN MENGHADAPI BENCANA - Pratama, I Gede Deva Wira; Ginting, Richard Togaranta; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 2 No 2 (2022), 2022)
Libraries as information provider institutions cannot be separated from the threat of disaster. The occurrence of disasters cannot be predicted by time, so it is very important for librarians to design strategies in dealing with the threat of disasters. The phenomenon that occurs is that not all libraries have a strategy to prevent disaster threats. This study aims to minimize the losses suffered by the library due to disasters. The author uses the literature study method. Library strategies in dealing with disasters through planning and disaster management can be divided into 4 (four) namely: Prevention, Planning, Response, Recovery.